Study of the poetic language in the poetry of Ibn Hammad Al-Adawi according to Todorov’s poetic theory - Ashura poems as an example - Hisham Taha Zaidan; Dr. Yahya Marouf; Dr. Torg Zaini,; Dr. Peyman Salehi (Journal of College of Education, 2024)
The concept of poetics has spread in the discussions of Western critics within very diverse and different cultural and critical contexts, which indicates the diversity of its fields, the multiplicity of its aspects, and the difficulty of confining it to a specific aspect. The truth is that different fields of knowledge competed with it, which was demonstrated by the linguistic field, which limited the angle of view to the linguistic phenomenon, and it appeared from This aspect relates the concept of poetics to both oral and written discourse, and it was not limited to poetry, but included all types of literature, and not only that, but it allowed all of that to relate to types of art in general, as long as the linguistics limited it to expressing the poetic function and its relationship to the various linguistic functions. Perhaps the most important achievement achieved by Todorov at the level of literary and critical studies is limited to the concept of poetics, which means a set of laws through which literature is studied, and these laws are what determine the literaryness of literature, and therefore the main task of these laws is to reveal the qualitative characteristics that distinguish discourse. Literary literature, and it does not study the mechanisms of discourse or the components that make up literature. Poetics, according to Todorov, is not an independent science in and of itself. Rather, it is related to various forms of literature, whether prose or poetry. Poetics does not work in isolation from the rest of the other sciences, but rather uses them and intersects with them. This is why it is included in A bit of ambiguity and ambiguity, but the feature of his poetics was towards structural application, and at the same time it extended to the field of literary science. This study seeks, taking advantage of the structural approach in its formal and formative branches, to shed light on the poetics of language according to Ibn Hammad al-Adawi according to Todorov’s poetic theory. Since I assimilated Ibn Hammad’s poems based on the narratives he heard, sometimes another story is told at the heart of each story, and Todorov’s theory is Cognitive narration is appropriate for it, and the results of the study indicate that the narrative structure of poems depends on one or several main events, and these events are placed. Together in the same order, the dominant style of the stories is serial, and these stories are found in the poems of Ibn Hammad. In this research, two poems related to the Ashura incident were examined, the suggestions of which represent 83% of the sentences are news and the obligatory sentences. 15.5% of the sentence and developmental sentences represent 0.8% of the sentence.